2004
DOI: 10.1016/j.jacc.2003.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Predischarge B-type natriuretic peptide assay for identifying patients at high risk of re-admission after decompensated heart failure

Abstract: High predischarge BNP assay is a strong, independent marker of death or re-admission after decompensated CHF, more relevant than common clinical or echocardiographic parameters and more relevant than changes in BNP levels during acute cares.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
3
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(160 citation statements)
references
References 36 publications
10
138
3
9
Order By: Relevance
“…Although some indicators, including sodium and BNP levels, are considered to be useful to predict cardiac events, it has been reported that few indicators evaluated at the decompensated stage are independent prognostic markers. For example, a high BNP level at discharge is generally considered to be a strong independent marker of death or re‐admission for heart failure 37, 38. However, the prognostic impact of BNP level on admission on ADHF appears to be weak and is less than that of BNP level at discharge after appropriate treatment for ADHF.…”
Section: Discussionmentioning
confidence: 99%
“…Although some indicators, including sodium and BNP levels, are considered to be useful to predict cardiac events, it has been reported that few indicators evaluated at the decompensated stage are independent prognostic markers. For example, a high BNP level at discharge is generally considered to be a strong independent marker of death or re‐admission for heart failure 37, 38. However, the prognostic impact of BNP level on admission on ADHF appears to be weak and is less than that of BNP level at discharge after appropriate treatment for ADHF.…”
Section: Discussionmentioning
confidence: 99%
“…NT‐proBNP (Elecsys 2010 analyzer, Roche Diagnostics, Indianapolis, IN) and copeptin and MR‐proANP (both on the KRYPTOR system) were measured centrally with the support of BRAHMS/Thermo Fisher, Germany. MR‐proADM was measured using an automated sandwich chemiluminescence immunoassay on the KRYPTOR system, as previously described 18, 19. For MR‐proADM, the limit of quantification was 0.23 nmol/L; the within‐run imprecision (coefficient of variation) was 1.9%, and the between‐run imprecision (coefficient of variation) was 9.8%.…”
Section: Methodsmentioning
confidence: 99%
“…The role of BNP and uric acid has been well established in numerous studies in patients with HF. High BNP levels are associated with higher NYHA class and worse outcomes [6]. BNP is measured as a screening test to identify asymptomatic patients with left ventricular dysfunction and early HF [7].…”
Section: (37)mentioning
confidence: 99%